Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2021)
Dear colleagues, At present, we are still hoping to escape from the shock of the pandemic in the near future while also expecting the possibility of a third wave. Meanwhile, let us turn to a new issue of our journal.